Kajian yuridis instruksi Wakil Gubernur DIY tentang penyeragaman kebijakan pemberian hak atas tanah terhadap WNI non pribumi - Nurul Fatimah; F Romana Harjiyanti; Erna Sri Wibawanti (Kajian Hasil Penelitian Hukum, 2019)
In Yogyakarta Non-Indigenous Indonesian Citizens may not own land with proprietary rights, this is based on the Deputy Governor s Instruction No.898 I A 1975 concerning Univormity of Policy on Granting of Land Rights Against Non-Indigenous Indonesian Citizens, in reality the Deputy Governor’s Instruction is still valid to date although DIY has fully enacted the LoGA since 1984.This research is normative legal research. This study uses primary legal material in the form of applicable legislation and secondary legal material in the form of legal literature. This study uses a legislative approach that is used to review and analyse all laws and regulations that have relevance to the legal issues being addressed. Based on the research result obtained data that the land office in DIY still applies the Deputy Governor’s instruction No.898 I A 1975 so that non-native Indonesian citizens will not be given land with a status of ownership rights, and seen from the hierarchy of legislation the Deputy Governor s instruction should be No. 898 I A 1975 may not defeat the Law 1945 Constitusion of the Republic of Indonesia, the LoGA, and the Citizenship Act where the Deputy Governors Instruction is under the Act. This also violates the principle of Lex Superior Derogate Inferiori the higher Act defeats the Law under it.